Serum 25-hydroxyvitamin D and biochemical markers of bone metabolism in patients with juvenile idiopathic arthritis - Munekata, R.V. (Associação Brasileira de Divulgação Científica, 2013)
Our objective was to evaluate the concentrations of serum 25-hydroxyvitamin D [25(OH)D], serum calcium, serum phosphorus, alkaline phosphatase, and parathormone (PTH) in patients with polyarticular juvenile idiopathic arthritis (JIA) and to associate them with disease duration and activity, bone mineral density and use of medications. In a cross-sectional and controlled study, 30 patients with polyarticular JIA were evaluated and compared to 30 healthy individuals matched for age and gender. Clinical status, anthropometry, laboratory markers in both patients and controls, and bone mineral density, only in the patients, were measured. Of the 30 patients included in the study, 23 (76.7%) were female and 16 (53.3%) non-Caucasian; mean age was 14 years (range = 4 to 20 years). Mean disease duration was 5 years (range = 1 to 12 years). The mean concentrations of serum albumin-corrected calcium (9.04 ± 0.41 mg/dL) and alkaline phosphatase (153.3 ± 100.1 IU) were significantly lower in patients with JIA than in controls (P < 0.0001 and P = 0.001, respectively). No differences in 25(OH)D, PTH or serum phosphorus were observed between JIA and control subjects. Regarding 25(OH)D concentration, 8 patients (26.7%) and 5 controls (16.7%) had 25(OH)D concentrations compatible with deficiency (lower than 20 ng/mL) and 14 patients (46.7%) and 18 controls (60%) had concentrations compatible with insufficiency (20-32 ng/mL). These values were not associated with disease activity, use of medications or bone mineral density. We observed a high frequency of 25(OH)D insufficiency and deficiency in the study sample. The compromised bone metabolism emphasizes the importance of follow-up of JIA patients.